The effect of telerehabilitation on activity performance and participation in daily life in children with developmental coordination disorder: A randomized controlled trial - Mazlum Uruc; Burak Menek (PLoS ONE, 2025)
Background Developmental Coordination Disorder (DCD) is a neurodevelopmental condition that adversely impacts motor skills, sensory processing, and daily activity participation. Telerehabilitation has recently emerged as a promising method to improve therapy access and foster family involvement. This study investigated the effects of integrating telerehabilitation with sensory-based intervention on motor performance, sensory processing, and participation in children with DCD. Methods This randomized controlled trial included 20 children aged 3–7 years with a confirmed diagnosis of DCD. Participants were randomly assigned to either a sensory-based intervention (SBI) group or a telerehabilitation sensory-based intervention (TBSI) group. Both groups received weekly face-to-face sensory-based therapy for eight weeks. Additionally, the TBSI group participated in 30-minute weekly home-based telerehabilitation sessions. Outcome measures included the Canadian Occupational Performance Measure (COPM), the Functional Independence Measure for Children (WeeFIM), and the Dunn Sensory Profile. Results Both groups demonstrated statistically significant improvements; however, the TBSI group showed greater gains in WeeFIM motor, cognitive, and total scores as well as COPM performance and satisfaction scores (p < 0.01). Furthermore, larger improvements and greater effect sizes were observed in the sensory processing subdomains of the TBSI group. Parental training and active participation appeared to enhance the effectiveness of the telerehabilitation program. Conclusions Telerehabilitation is an effective intervention for improving motor and cognitive functions, sensory processing, and daily life participation in children with DCD. The findings support the integration of telerehabilitation into sensory-based approaches as part of a holistic model of care in occupational therapy practice. Trial registration Clinicaltrials.gov NCT06977256.